Isolated Paresis of Laryngeal Adduction: What Are the Laryngoscopic and Stroboscopic Findings?. (25th November 2018) - Imamura, Rui; Marcelo, Agatha M.; Tsuji, Domingos H.
Abstract : Objectives/Hypothesis: This study aimed to describe the videolaryngostroboscopic (VLS) findings in a cohort of patients with isolated paresis of laryngeal adduction and identify predictive variables that may be related to voice recovery. Study Design: Chart review and VLS analysis of dysphonic patients diagnosed with isolated paresis of laryngeal adduction by laryngeal electromyography (LEMG). Methods: Demographic, clinical, VLS, and LEMG findings were analyzed according to the outcome of dysphonia. Results: There were 17 patients, 12 males (70.6%), mean age of 46.6 years, with median dysphonia duration of 4 months (range, 1–60 months) included in the study. In all patients, gross movement of both vocal folds were normal. Laryngoscopy showed limited adduction of the ipsilateral ventricular fold, contralateral interarytenoid region deviation, and vocal fold atrophy in 100%, 94.1%, and 76.5% of patients, respectively. VLS findings included: impairment of glottic closure (94.1%), phase asymmetry (94.1%), and reduced mucosal wave on the affected side (76.5%). Predictors of good voice outcome were sudden onset ( P  = .012), duration of dysphonia on presentation shorter than 5 months ( P  = .005), and absence of polyphasic potentials on LEMG ( P  = .041). Conclusions: Findings on VLS as described suggest isolated paresis of laryngeal adduction and should warrant indication of LEMG for definite diagnosis. Voice improvement may be related to clinical and LEMG findings. Level of Evidence: 4 Laryngoscope, 129:919–925, 2019